Decoding Consumer Behaviour in Indonesian E Commerce: A Stimulus-Organism-Response Analysis - Cheng, Kin Meng; Wijaya, Lianna; Ng, Kah Choon; Anthonysamy, Lilian (Journal of Telecommunications and the Digital Economy, 2024)
Indonesia holds a significant position in Southeast Asian e-commerce, witnessing notable shifts in consumer shopping patterns owing to the rapid expansion of online markets. This study concentrates on understanding e-commerce dynamics within Indonesian suburban areas. This research aims to unravel the hindering factors in Indonesian e-commerce, employing the Stimulus-Organism-Response framework to decode the intricate relationships between stimuli, organisms, and responses. This study endeavours to comprehend the intricate perceptions and behavioural tendencies exhibited by a cohort of 280 individuals by implementing a targeted quantitative questionnaire. The investigation seeks to scrutinize the impact of security, privacy, perceived risk, and cognitive trust on the attitudes and behavioural intentions of suburban consumers engaging in e-commerce activities. Employing SmartPLS as the analytical framework and utilizing Partial Least Squares Structural Equation Modelling (PLS-SEM), the research aims to investigate the causal relationships among key factors in the Indonesian suburban e-commerce industry. With a focus on the suburban population, this empirical study will offer comprehensive insights into the intricate dynamics of e-commerce. The findings are expected to contribute meaningful insights to the growing domain of e-commerce research and offer practical recommendations to foster the development of a resilient and thriving e-commerce ecosystem in Indonesia.